Myocardial function during bradycardia events in preterm infants. (July 2016) - de Waal, Koert; Phad, Nilkant; Collins, Nick; Boyle, Andrew
Abstract: Background: Transient bradycardia episodes are common in preterm infants and often secondary to apnea. Decreased ventilation with resultant hypoxemia is believed to be the predominant mechanism. Sudden bradycardias without apnea are also reported, possibly due to vagal stimulation. Point of care ultrasound is used to diagnose and follow cardiovascular complications in preterm infants. Inadvertently, the operator would sometimes capture bradycardia events. This study reports on left ventricular function during such events. Methods: We retrospectively reviewed our cardiac ultrasound database for bradycardia events. Apical four or three chamber images before, during and after a bradycardia event were analysed with speckle tracking software which provides systolic and diastolic parameters of myocardial motion, deformation and volume. Results: Over a 2 year period, 15 bradycardia events were noted in 14 patients with a median gestational age of 26 weeks (range 23 to 29). Heart rate decreased by an average of 43% (171/min to 98/min). Myocardial velocity and longitudinal strain rate during the atrial component of diastole were reduced during bradycardia. Longitudinal strain during systole was increased and radial deformation was unchanged. Ventricular volumes and ejection fraction did not change. Most parameters returned to baseline values after the event. Longitudinal systolic strain rate remained lower and stroke volume was 12% higher compared to baseline. Conclusion: Parameters of systolic contractility and stroke volume were maintained and parameters of atrial contractility were reduced during mild to moderate bradycardia in preterm infants. Bradycardia reduces total cardiac output with a compensatory increase detected following the event. Highlights: Myocardial function during sudden bradycardia events in preterm infants has not been described Speckle tracking analysis is a novel technique that can be applied retrospectively to examine myocardial function in detail Systolic function and stroke volume were maintained during moderate bradycardia events in preterm infants and atrial contractility was reduced